ANALISIS PEMETAAN ZONA KONSERVASI AIR TANAH DI PROVINSI SULAWESI SELATAN MENGGUNAKAN APLIKASI QGIS - Ammar, Abu; Askar,; Munir HB, Abd.; Sahara, (JFT: Jurnal Fisika dan Terapannya, 2022)
This study is titled Mapping Analysis of Groundwater Conservation Zones in South Sulawesi Province Using QGIS Application. This study aims to digitize the map of groundwater conservation zones in 13 regencies/cities in South Sulawesi Province and to find out the division of groundwater conservation zones in 13 regencies / cities in South Sulawesi while calculating the area of each zone. The method used in this study is to use data processing methods, where secondary maps in jpeg form are digitized and then analyzed to obtain results in the form of zone division and area of each zone. From the results of research that has been obtained, there are 5 types of groundwater conservation zones, namely critical zones, rare zones, vulnerable zones, safe zones, and addition zones. In 13 regencies/cities in South Sulawesi Province the most extensive zone is a safe zone with an area of 818912.42 hectares. However, the second largest zone (59626,923 hectares) is a vulnerable zone where in this zone can no longer absorb properly. For this reason, there needs to be a preventive way to overcome the problem.